2011
DOI: 10.1590/s0104-11692011000700003
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo y de protección relacionados con el consumo de sustancias psicoactivas en estudiantes de enfermería

Abstract: estudiantes. Los dominios "preconceptos y valoración", "permisividad social y accesibilidad a SPA", "habilidades sociales y de autocontrol" son factores de riesgo en casi el 100% de los encuestados para el consumo de drogas. La "Espiritualidad" y "satisfacción con relaciones interpersonales" son los dominios protectores predominantes. Con base en los datos, se puede presumir que los estudiantes no dimensionan los riesgos frente al consumo de alcohol y tabaco, lo que los lleva a considerar su consumo como norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 4 publications
0
11
0
16
Order By: Relevance
“…In particular, several authors agree that there is a greater likelihood of an early onset of marijuana use in these areas (Díaz-Negrete et al, 2008;Peñafiel, 2009;López et al, 2010;Morales et al, 2011). In some cases, this early onset increases the likelihood of using other substances with a greater addictive potential (Ellickson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, several authors agree that there is a greater likelihood of an early onset of marijuana use in these areas (Díaz-Negrete et al, 2008;Peñafiel, 2009;López et al, 2010;Morales et al, 2011). In some cases, this early onset increases the likelihood of using other substances with a greater addictive potential (Ellickson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important among older students, since they are generally more exposed to use and its associated risks (Morales et al, 2011), in addition to the fact that they wish to experience new feelings and may have to cope with adverse situations (Sierra et al, 2005;Duarte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The onset of drug use is associated with diverse risk factors, within the main are found, low and high self-esteem, friends and parents that are consumers, under self-control, low school adherence, dysfunctional family relationships, curiosity, lack of religious support, Social permissiveness and accessibility. 3,[5][6][7] Recently diverse studies have documented the association between bullying and drug consumption; bullying is defined as the intentional aggression that persists in time and leads to an imbalance of power. 8 In a longitudinal study carried out by Kim, Catalano, Haggerty and Abboutt 9 it showed how the children that were victims of bullying were associated significantly to excessive alcohol and marihuana consumption at the age of 21.…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los temas de interés frente a esta problemática ha sido identificar los factores de protección y de riesgo asociados, los cuales han sido definidos por la literatura científica como "una serie de circunstancias o eventos de naturaleza biológica, psicológica, social, o ambiental cuya presencia o ausencia modifican la probabilidad de la aparición de un problema" (Morales, Plazas, Sánchez & Arena;2011, p. 675).…”
unclassified